Parent–child relationships and psychological distress: survey of parents from low-income families after the COVID-19 pandemic - Wong, Li Ping; Alias, Haridah; Farid, Nik Daliana Nik; Yusop, Sofia Md; Musa, Zuhrah; Hu, Zhijian; Lin, Yulan (Frontiers in Public Health, 2023)
Introduction This study aims to shed light on parent–child relationships and the psychological health of parents from low-income families after the easing of the COVID-19 pandemic restrictions. Methods This cross-sectional study recruited 553 parents of children aged 13–24 years in low-income community settings. The Parent–Child Conflict scale of the Parental Environment Questionnaire (PEQ) was used to measure parent–child conflict. Psychological distress was assessed using the Depression, Anxiety, and Stress Scale short form (DASS-21). Results The study revealed a low level of parent–child conflict in the overall study population, with a median PEQ of 48.0 (interquartile range [IQR] 36 to 48). Concerning demographics, married parents reported a likelihood of having a higher level of parent–child conflict over 3 times higher than single parents (OR = 3.18 95%, CI 1.30–7.75). More parent–child conflicts were also found in parents aged 60–72 years old who were unemployed, retired, or housewives and from lower-income groups. In regard to lifestyle factors, a higher level of physical activity and having enough sleep were associated with lower levels of parent–child conflict. Only approximately 1% of the participants reported symptoms of depression, anxiety, or stress. Discussion Low risk exists for parent–child conflict and psychological sequelae following the easing of the COVID-19 pandemic restrictions, which could be due to various support measures implemented by the government. Vulnerable parents identified as being at risk of parent–child conflict warrant attention in future advocacy efforts.